Analysis of Representative Speech Acts on the Education Portal Channel " Summary of Indonesian Language Material Class 7 K-13 " - Anis Ulfah; Nurul Jumrah; Yesi Dwi Paraswati; Asih Kusumawati; Asep Purwo Yudi Utomo; Yerry Mijianti; Rossi Galih Kesuma (International Journal of Educational Development, 2024)
Speech acts in pragmatic science are divided into several types, one of which is representative speech acts. Speech acts that bind the speaker to the truth of what he says are representative speech acts. Speeches that include speech acts can be found in learning videos. Based on this, this study analyzes the representative speech acts contained in the learning video. The data used in the research is in the form of learning videos in the "Summary of Indonesian Language Materials Class 7 K-13" playlist on the Youtube channel "Edukasi Portal". This study aims to provide exposure and describe various representative speech acts contained in the data source. The method used in this study is a qualitative descriptive method. It was found in Chapter 1 ''Description Text'' material, 1 0 data were produced, 1 2 data was found in Chapter 2 ''National Text'', 9 representative speech data were found in Chapter 3 ''Procedural Text'' , and 12 speech data were found. on the material of Chapter 4 ''Text of Observation Results'' and as many as 12 data on the material of Chapter 5 ''People's Poetry''. This research is useful for readers in facilitating understanding of representative speech acts. With the analysis of representative speech acts, it is hoped that readers can fully understand and comprehend representative speech acts. This research is useful for readers in facilitating their understanding of representative speech acts .